Determination of the composition of pharmaceutical substances used in drugs with antiarrhythmic activity - A. V. Rogov; G. V. Mokrov (Фармакокинетика и Фармакодинамика)
Cardiac arrhythmias are the most common pathologies of the cardiovascular system. Allapinin® and Allaforte® from “Pharmcenter VILAR” are effective IC-class antiarrhythmic agents. The main component of these drugs is a pharmaceutical substance with INN: lappaconitine hydrobromide, which in addition to lappaconitine hydrobromide itself, contains impurities of other diterpene alkaloids. This work is devoted to a detailed analysis of the alkaloid composition of a new pharmaceutical substance isolated from roots and rhizomes, as well as from the aerial part of plants of the genus Aconite (monkshood, wolfsbane) of the Ranunculaceae family (buttercups) using chromato-mass spectrometry and NMR spectroscopy. In addition, an assessment was made of the quantitative ratios of alkaloids in several samples of pharmaceutical substances isolated from different batches of medicinal plant raw materials.